2014
DOI: 10.1016/j.apnu.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Potential Long-Term Effects of a Mind–Body Intervention for Women With Major Depressive Disorder: Sustained Mental Health Improvements With a Pilot Yoga Intervention

Abstract: Despite pharmacologic and psychotherapeutic advances over the past decades, many individuals with major depressive disorder (MDD) experience recurrent depressive episodes and persistent depressive symptoms despite treatment with the usual care. Yoga is a mind-body therapeutic modality which has received attention in both the lay and research literature as a possible adjunctive therapy for depression. Although promising, recent findings about the positive mental health effects of yoga are limited because few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 31 publications
3
98
0
Order By: Relevance
“…In a study comparing yoga alone, antidepressant medication alone and yoga along with antidepressants, more patients in the yoga groups had a decrease in cortisol levels, and in the yoga alone group the cortisol decrease correlated with decreased depression scores [64]. In a longitudinal follow-up study, the effects of yoga were seen to last at least to the end of one-year [65]. Although the findings of the study may not be generalizable because the sample size was limited, the data suggest that yoga may have a sustained effect on depression and its symptoms including ruminations, stress, anxiety and quality of life.…”
Section: Depressionmentioning
confidence: 94%
“…In a study comparing yoga alone, antidepressant medication alone and yoga along with antidepressants, more patients in the yoga groups had a decrease in cortisol levels, and in the yoga alone group the cortisol decrease correlated with decreased depression scores [64]. In a longitudinal follow-up study, the effects of yoga were seen to last at least to the end of one-year [65]. Although the findings of the study may not be generalizable because the sample size was limited, the data suggest that yoga may have a sustained effect on depression and its symptoms including ruminations, stress, anxiety and quality of life.…”
Section: Depressionmentioning
confidence: 94%
“…Sixty studies (n = 2909) showed a significant large-size effect of exercise on depressive symptoms (ES = 0.78, 95% CI 0.58-0.98, p < 0.0001; Fig. 3 95,190,207,225] and two studies [99,193] with high risk of bias decreased the overall ES to a medium effect (k = 43 n = 2430, ES = 0.47, 95% CI 0.32-0.62, p < 0.0001). Heterogeneity reduced to moderate to high [Q(42) = 130.55, p < 0.0001; I 2 = 68%].…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…Nine hundred ninety-seven non-duplicate records were retrieved by literature search; 979 of which were excluded because they were not randomized, did not include participants with major depression and/or did not include yoga as an intervention. Seventeen full-texts were assessed for eligibility (Butler et al, 2008;Field et al, 2013a, b;Field et al, 2012;Gangadhar et al, 2013;Kinser et al, 2013;Kinser et al, 2014;Lavretsky et al, 2013;Naveen et al, 2013;Naveen et al, 2016;Rohini et al, 2000;Thirthalli et al, 2013;Uebelacker et al, 2016); and 8 articles were excluded because they were either not randomized (Naveen et al, 2013;Naveen et al, 2016;Thirthalli et al, 2013), no non-yoga control group was used (Rohini et al, 2000), the included participants were not diagnosed with a depressive disorder (Lavretsky et al, 2013), they were diagnosed with a depressive disorder but less than 75% with major depressive disorder (Butler et al, 2008), or it was unclear with what depressive disorder the participants were diagnosed (Field et al, 2013a, b;Field et al, 2012). One additional full-text was excluded because it was originally planned as an RCT but later changed to a non-randomized controlled study design and only a minority of participants actually were randomized (Gangadhar et al, 2013).…”
Section: Literature Searchmentioning
confidence: 99%
“…One additional full-text was excluded because it was originally planned as an RCT but later changed to a non-randomized controlled study design and only a minority of participants actually were randomized (Gangadhar et al, 2013). Eight articles reporting seven RCTs on yoga for participants with major depressive disorder, encompassing 240 participants, were finally included in the analysis (Figure 1) (Janakiramaiah et al, 2000;Kinser et al, 2013;Kinser et al, 2014;Sarubin et al, 2014;Schuver and Lewis, 2016;Sharma et al, 2016a;Sharma et al, 2005;Uebelacker et al, 2016).…”
Section: Literature Searchmentioning
confidence: 99%